2008
DOI: 10.1029/2007gl032733
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional radar observation of a submillimeter meteoroid fragmentation

Abstract: [1] We present and discuss two examples of pulsating meteor events observed with the tristatic 930 MHz EISCAT UHF radar system. One of them provides the first strong observational evidence of a submillimeter-sized meteoroid breaking apart into two distinct fragments. The received power fluctuates regularly in the time profiles of all three receivers, but the fluctuation frequencies are different. The pulsations are interpreted as being due to interference from two distinct scattering centers and the three dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…Kero et al (2008a) have shown that these are sometimes caused by interference between echoes from two or more distinct scattering centers simultaneously present in the radar beam. The Doppler shift of the returned signal from two simultaneously illuminated meteoric fragments is proportional to a weighted arithmetic mean of their Doppler velocities, with weights equal to the square root of their RCSs.…”
Section: Radial Deceleration Due To Finite Beamwidthmentioning
confidence: 99%
“…Kero et al (2008a) have shown that these are sometimes caused by interference between echoes from two or more distinct scattering centers simultaneously present in the radar beam. The Doppler shift of the returned signal from two simultaneously illuminated meteoric fragments is proportional to a weighted arithmetic mean of their Doppler velocities, with weights equal to the square root of their RCSs.…”
Section: Radial Deceleration Due To Finite Beamwidthmentioning
confidence: 99%
“…With head echo observations, parameters such as velocity and deceleration components along the radar beam, altitude of occurrence and rates can be obtained directly (Kero et al 2008a). Tristatic measurements allow observing fragment formation (Kero et al 2008b) and estimating the meteoroid mass and size with high accuracy (Kero et al 2008c). These measurements also lead to a better derivation of the magnitude and orbit determinations for individual meteors (Szasz et …”
Section: Radar Meteor Observationsmentioning
confidence: 99%
“…In contrast to this, fragmentation of radar meteor echoes has become a subject of discussion in the radar meteor community only in the past few years with evidence of fragmentation being found in head echo observations carried out using high power large aperture (HPLA) radars (Kero et al 2008;; Malhotra and Mathews ). Relatively few studies have been conducted on fragmentation and its effects on radar specular trail echoes.…”
mentioning
confidence: 96%